PERAN INSTITUSI LOKAL DALAM PENINGKATAN EKONOMI NAGARI DIMASA PANDEMI - Indraddin Indraddin; Zeni Eka Putri; Retno Anggraini (Universitas Andalas, 2021)
This research aims to explore the work of local institutions in overcoming the impact of the covid-19 outbreak and improving the economy of the community in Nagari Sungai Pinang. The concept of local institutions in this study is related to values, norms, and habits in society, both at the individual, community, and institutional levels. This study uses a qualitative approach, with data collection techniques being in-depth interviews, observation, and FGD. The data were analyzed with the principles of qualitative data analysis from Miles and Huberman. The results of the study were that local institutions related to values and norms worked when the corona outbreak came. The value of helping and working together seems to encourage people to solve their own problems. Meanwhile, the value related to institutions is the role of the Nagari Traditional Kerapanan, Bundo Kanduang, and Parik Paga Nagari institutions in overcoming the COVID-19 outbreak. These local institutions are active in improving the economy of the Sungai Pinang community in agriculture, fishing, and the tourism sector. The role played by these local institutions is to encourage community members to work together to help each other, and to apply the value of land use in the agriculture, tourism, and fishing sector